Cattle Health Management through Vitamin B-Complex Injection Program in Konda District, South Konawe Regency - Saili, Takdir; Asminaya, Nur Santy; Badaruddin, Rusli; Syamsuddin, Syamsuddin; Aka, Rahim; Zulkarnaian, Deki; Munadi, La Ode Muh (Jurnal Pengabdian Masyarakat Formosa, 2024)
Community service activities carried out by the Postgraduate Lecturer Team and Faculty of Animal Husbandry in collaboration with the Livestock and Animal Health Service Office and UPTD livestock breeding focusing on Lawoila Village, Konda Subdistrict, South Konawe District. The aim is to introduce livestock health management to improve cattle productivity, livestock health, and ensure livestock products have the desired quality standards. The methods applied included observation, counseling, and evaluation. Results showed that the livestock health service was well received by farmers in Lawoila Village. The local community showed high enthusiasm in understanding livestock health management with the hope of improving overall livestock productivity. This effort reflects an effective collaboration between academia, local government, and the community in improving the welfare of farmers and strengthening the livestock sector.